Strategic management concepts and cases : a competitive advantage approach / Fred R. David - David, Fred R. (Pearson, 2013)
The global economic recovery has created a business environment that is quite different and more complex than before. This new edition of the textbook reveals how to conduct effective strategic planning in this new world order.